Age and socioeconomic status are associated with contraceptive choice among long-term reversible contraceptive method users in Indonesia (analysis of 2017 Indonesia demographic health survey data): English - Pasundani, Nita Adhani; Mutiara Solechah; Anida Izatul Islami (Jurnal EduHealth, 2024)
Indonesia's increasing population will bring various problems in the future, besides that the maternal mortality rate (MMR) is still high, one of which is caused by too close a birth distance so it is necessary to control or control population growth through family planning programs. The purpose of this study was to determine the relationship between age and socioeconomic status with contraceptive selection in users of reversible long-term contraceptive methods in Indonesia, analyzed by the 2017 IDHS. The design used in this study was cross sectional with a research sample of 8,238, samples were taken based on total sampling of data that included the inclusion and exclusion criteria of the study. Bivariate and multivariate analysis using logistic regression. The results showed that 58.4% used implants, 41.6% used IUDs. This study shows that there is a relationship between age and socioeconomic status with contraceptive selection in users of long-term reversible contraceptive methods